Action research progress on incorporating augmented reality into courses: Taking digital publishing as an example / Siek Hwee Ling - Siek, Hwee Ling (Universiti Teknologi MARA, 2020)
This paper is based on the reflexivity approach towards teaching and learning the action research process of a Digital Publishing subject. The initial motivation was developing a new teaching format, to guide students in the integration of Augmented Reality in a print book because the current digital trajectory allows prospective designers to showcase their uniqueness. Action research was engaged to explore factors that affected the planning and professional growth of the researcher, as the process underwent a constant adjustment which promote educational innovation in line with the accumulation of experiences which aimed to narrow the gap between academic aspirations and market reality. During the course of this study, professional growth was shown after introspection as when the researcher was encouraged from students evaluation and then to explore the cross-disciplinary collaboration with colleague from communication department and understand the marketplace and consumer needs which in turn provided the required momentum to go further by identify the next cross-discipline potential collaborator in Music and Audio technology department, to further fine tune the teaching format and development for next cohort, as instructors can rely on each other's expertise to solve problems and provide support. And, researcher also suggested that should publicly disseminate their knowledge of action research through research reports.